Liquid Drop Model for Investigating the Outer Crust of Neutron Star - Fitrishia, Feni; Sulistyani, Eko Tri; Budhi, Romy Hanang Setya (Proceeding International Conference on Science and Engineering, 2019)
The properties of outer crust of cooling neutron star by using Liquid Drop Model approximation has been studied. Th is mass model is used to derive the properties of outer crust of neutron star matter such as total energy of system, equation of state (relationship between pressure and density), and composition of the outer crust. The properties of the outer crust are studied under the assumption that neutron star has created for long time and the matter in neutron star is in its ground state. The composition of the outer crust consists of ions Z arranged in a lattice and free electrons e, so that the total energy of the system consists of three contributions: the mass-energy of the nuclear, the energy of electrons and lattice. The equation of state (the relationship between pressure and density) shows that the pressure increases with increasing density in the outer crust layer. With a simple model based on liquid drop model, it is known that the outer crust is composed of nuclei which are at Z ? 20-50, with 56Fe core at the upper layer, and 154Cd core at the lowermost layer of the outer crust.